1996
DOI: 10.1063/1.117598
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of interface trap creation by hot-electrons in AlGaAs/GaAs high electron mobility transistors

Abstract: We report on the hot-electrons induced degradation in AlGaAs/GaAs high electron mobility transistors (HEMTs), consisting of a decrease in the drain current and an increase in the parasitic drain resistance. The amount of the degradation is proportional to the impact-ionization rate which is related to the electron energy. Transconductance dispersion measurements and drain current deep level transient spectroscopy (DLTS) have been used to identify interface traps which are located at the AlGaAs/GaAs interface i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Assuming exponential decay of the detrapping current the detrapping time constant is estimated to be 53.2 s and is in agreement with the value mentioned in [8]. The detrapping time is expressed as [11]: td « l/{(r"VthNc exp\-iEc-Et)/kT]}, where iTn is the electron capture cross section, vth = \/3kT/ml is the thermal velocity, m* is the electron effective mass in GaN, Ec and Et are the conduction and trap energy levels, respectively. With m* = 0.2mo, where ruo is free electron mass, Nc = 1 x 10^^ cm~^, and <T" = 10"^^ cm~^,£'t is found to be located at 0.78 eV below Ec at room temperature.…”
Section: Rds Tdsupporting
confidence: 59%
See 1 more Smart Citation
“…Assuming exponential decay of the detrapping current the detrapping time constant is estimated to be 53.2 s and is in agreement with the value mentioned in [8]. The detrapping time is expressed as [11]: td « l/{(r"VthNc exp\-iEc-Et)/kT]}, where iTn is the electron capture cross section, vth = \/3kT/ml is the thermal velocity, m* is the electron effective mass in GaN, Ec and Et are the conduction and trap energy levels, respectively. With m* = 0.2mo, where ruo is free electron mass, Nc = 1 x 10^^ cm~^, and <T" = 10"^^ cm~^,£'t is found to be located at 0.78 eV below Ec at room temperature.…”
Section: Rds Tdsupporting
confidence: 59%
“…Kunihiro et al [9] have reported recovery of current collapse with measurements with 10 s hold time as the electrons get more time to be detrapped. At high frequencies, when the detrapping time is comparable to or greater than the signal period, traps cannot respond quickly enough to the applied voltage giving rise to frequency dispersion in device transconductance and output resistance [10], [11]. For microwave circuit design, the frequency dispersion of electrical characteristics is important, as trapping effects reduce the transconductance and output resistance significanfly from their dc values.…”
Section: Gan-based Heterojunction Field Effect Transistors (Fets)mentioning
confidence: 99%
“…11 the static drain current characteristics at constant gate voltage for the fresh device and for the devices after the 24-h stresses. It is evident that, in both cases, an important current collapse [11] occurs which can be related to trap creation induced by the forced stress conditions [12]. As a matter of fact, also in the present case, the average value of the gate current appears a valuable indicator for quantifying device degradation under dynamic operation, that is: increasing values (in magnitude) of the average gate current unquestionably correspond to more severe device performance drop.…”
Section: Analysis Of the Experimental Resultsmentioning
confidence: 88%
“…Traps with similar activation energy and capture cross section have been previously identified as donorlike states in the GaN cap layer [7], [9], although this identification is questionable due to the very small capture cross section. However, such traps might be of surface or interface state types, which cannot be normally characterized by a simple activation energy [10]. Since the gate lag is measured under a drain bias of 4V , the applied electric field will lower the barrier of the traps (Poole-Frenkel effect) [6], [7].…”
Section: Resultsmentioning
confidence: 99%